(3NQjOI GdYLGFH haQjOI GdZQGFHs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s ((3YHO GdhLhGH GdOedjLi GdTGaYi s)
(3ChdgG (B:s
(3hHYO aEf NGdb GdNdb hGdHQjI hef dg GdGQGOI hGdeTjFI bO ejR Gdedhc hGdQYGI Yf ef Ohfge ef GdQYjI adPdc bO NUhG HGdgee GdYdjI s
(3BNQgG (B:s
(3jfJgi HLOhd ajg MSGH GdJZGdH hGdeZdhH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jTJed Ydi NQGFWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs